Wageningen UR Frontis Series
DOI: 10.1007/1-4020-5906-x_11
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Interventions in Breeding for Adaptation to Abiotic Stress

Abstract: Abstract. The physiological-trait-based breeding approach has merit over breeding for yield per se because it increases the probability of crosses resulting in additive gene action. While considerable investment in germplasm characterization is required, conceptual models of crop genotypes can be employed as research tools to quantify likely genetic gains associated with specific trait or in defining traits that may have generic value across different stresses. For example, deeper root growth that permits bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…Physiological trait based breeding approach has merit over breeding for yield per se because it increases the probability of crosses resulting in additive gene action (Reynolds and Trethowan, 2007). The process of incorporating new genetic diversity can be accelerated with suitable earlygeneration selection tools that enable the best progeny to be identified before costly yield trials are run.…”
Section: Differential Effects Of Post-flowering Drought Stress On Gromentioning
confidence: 99%
“…Physiological trait based breeding approach has merit over breeding for yield per se because it increases the probability of crosses resulting in additive gene action (Reynolds and Trethowan, 2007). The process of incorporating new genetic diversity can be accelerated with suitable earlygeneration selection tools that enable the best progeny to be identified before costly yield trials are run.…”
Section: Differential Effects Of Post-flowering Drought Stress On Gromentioning
confidence: 99%
“…Under such moisture stress conditions development of rapid, effective screening method is a major challenge for plant breeders (Khan et al, 2013;Mahmood et al, 2013;Subhani et al, 2012). Germplasm improvement for drought can be accomplished significantly through the use of physiological interventions in breeding (Reynolds and Trethowan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, Tim et al (2001) demonstrated that correlation between rate of reduction in kernel weight by current photosynthesis restriction and rate of reduction by drought stress is significant. Cutting of one or two thirds of leaf blade at V 8 in moderately irrigated plants significantly reduced Table 3), indicating that pre-anthesis source strength limitation reduces grain yield both through lower dry matter accumulation and by reducing the dry matter allocation efficiency to grain filling (Reynolds and Trethowan 2007). It seems that because of controlling the effect of pre-anthesis source strength on sink capacity (Figure 3), the grain set was reduced (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Improving attainable crop yields under stress conditions requires knowledge of yield formation physiological processes such as source-sink relationships (Reynolds andTrethowan 2007, Barnabas et al 2008). Thus, Yushiharu et al (1993) reported that three weeks after anthesis, both the chlorophyll and Rubisco contents were positively correlated with source to sink ratio.…”
mentioning
confidence: 99%